The causal association between body mass index and type 2 diabetes mellitus—evidence based on regression discontinuity design. Issue 8 (23rd April 2021) - Guo, Zhaoyan; Liu, Li; Yu, Fangfang; Cai, Yaning; Wang, Junyi; Gao, Yang; Ping, Zhiguang
Abstract: Objective: This study aimed to investigate and determine the precise causal association between body mass index (BMI) and type 2 diabetes mellitus (T2DM) using a regression discontinuity design (RDD). Methods: The cross‐sectional data of 8550 participants were from the China Health and Nutrition Survey (CHNS) in 2015. Influencing factors with statistically significant were selected with logistic regression analysis, and a risk prediction model was established to obtain the risk of individuals suffering from T2DM. RDD was performed with BMI as the grouping variable and the risk of individuals suffering from T2DM as the outcome variable. Results: The predictive factors in the T2DM risk prediction model were age, gender, BMI, habitation, education, physical activity level, preference for sugary beverages, walking, self‐evaluation health status and history of hypertension. The AUC (area under receiver operating characteristic curve) of the T2DM risk prediction model was 0.849 (95% CI: 0.833, 0.866). BMI was an independent risk factor for T2DM (OR = 1.109, p  < 0.001); at BMI = 31 kg/m 2, the risk of T2DM increased sharply by 5.03% ( p  = 0.006). Conclusions: There was a positive causal association between BMI and T2DM; when BMI = 31 kg/m 2, the risk of individuals suffering from T2DM was sharply increased.